The effect of school and peer connectedness on adolescent mental health outcomes during the COVID-19 pandemic: a longitudinal panel survey. (November 2021) - Widnall, Emily; Winstone, Lizzy; Plackett, Ruth; Adams, Emma; Haworth, Claire; Mars, Becky; Kidger, Judi
Abstract: Background: The COVID-19 pandemic, school closures, and social distancing measures have disrupted young people's daily routines, learning, and social relationships. We examine the changes in adolescent mental health over time and explore the relationship between how connected students felt to their school and peers before the pandemic and how this affected their mental health during school closures and on return to school. Methods: This is a longitudinal three-wave panel survey with students aged 13–15 years in 17 secondary schools across the South West of England. Students completed a self-report survey before the pandemic (October, 2019), during the first UK lockdown (May, 2020), and shortly after returning to school (October, 2020). Matched data across all three waves were available for 603 students. Anxiety and depression were measured using the Hospital Anxiety & Depression Scale (HADS). School connectedness was measured using six items adapted from the Psychological Sense of School Membership (PSSM) scale. Peer connectedness was measured using a seven-item subscale as published by Jose, Ryan, and Pryor (2012). The study was approved by the University of Bristol Medical School ethics committee (reference 84883). Findings: There was an overall decrease in anxiety score from before the pandemic (median 7, IQR 4–11) to during the first UK lockdown (median 6, IQR 3–10). Wilcoxon signed-rank tests indicated that this difference was statistically significant ( z =–7·061, p<0·0001). Anxiety levels then increased on return to school (median 8, IQR 4–11), which was also statistically significant (z=6·983, p<0·0001). No changes were observed for levels of depression over the three timepoints. Low school connectedness at baseline predicted a significant increase in anxiety when students returned to school (β 1·33, 95% CI 0·55–2·11; p=0·001). No significant association was found between low peer connectedness before the pandemic and anxiety levels on return to school (β 0·53, 95% CI –0·24 to 1·30; p=0·175). Interpretation: Our findings suggest that most students adapted well to school closures, and in fact experienced less anxiety than before the pandemic. Students who reported feeling poorly connected to school before the pandemic are likely to experience higher levels of anxiety on return to school. This study highlights the need for routine mental health and wellbeing monitoring in schools to identify key areas of support and to inform school-based public health interventions. Funding: The National Institute for Health Research (NIHR) School for Public Health Research (SPHR).